2020
DOI: 10.1111/cdev.13438
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Educational Interventions for Orphans and Vulnerable Children Affected by HIV/AIDS: A Meta‐Analysis

Abstract: Orphans and vulnerable children affected by HIV/AIDS (HIV OVC) are at risk for cognitive difficulties and lack of access to education. Interventions addressing cognitive or educational outcomes for HIV OVC worldwide were examined through systematic searches conducted from October 2016 to 2019. We examined the summative effectiveness of interventions and the specific effects of participant age and intervention length. Interventions targeting cognitive outcomes had a small, significant effect, with no effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
1
1
0
Order By: Relevance
“…Whereas previous studies have shown that age of CALHIV has a significant influence on VL suppression [6,16], in this study, there is no significant difference between VL suppression levels in all age-groups in comparison to the reference level of 1-4 years. This finding is similar to those from a systematic review and meta-analysis examining cognitive and educational interventions for OVC affected by HIV/AIDS by mention authors [17]. In our study, we found that interventions targeting educational outcomes had a significant effect on VL suppression.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas previous studies have shown that age of CALHIV has a significant influence on VL suppression [6,16], in this study, there is no significant difference between VL suppression levels in all age-groups in comparison to the reference level of 1-4 years. This finding is similar to those from a systematic review and meta-analysis examining cognitive and educational interventions for OVC affected by HIV/AIDS by mention authors [17]. In our study, we found that interventions targeting educational outcomes had a significant effect on VL suppression.…”
Section: Discussionsupporting
confidence: 92%
“…According to Banstola, Ogino and Inoue (2020), "self-esteem is an important aspect of mental health and it is believed to be one of the predictive factors for the psychological well-being of adolescents in their unique period of identity development" (p. 1). Indeed, many other previous studies have also found that, adequate psychosocial and educational support services offered to children and adolescents orphaned due to HIV and AIDS enabled them to fare well emotionally, socially, psychologically and academically (Muriuki, Andoh, Newth, Blackett-Dibinga, & Biti, 2016;Sitienei & Pillay, 2019b;Thomas, Ahmed, Tan, & Grigorenko, 2021;Visser, Zungu, & Ndala-Magoro, 2015). The Community and Youth Development Worker describes the psychosocial support programme offered through his sector as the one that provides group therapy activities for adolescents orphaned due to AIDS and other vulnerable children within the community.…”
Section: Discussionmentioning
confidence: 99%
“…The shock of maternal recent HIV diagnosis may have placed a major burden on these families, compounded by risk drivers which may have accounted for the HIV exposure in the first place, such as economic and food insecurity, or mental health struggles. This indicates that affected families may profit from additional support, including early cognitive interventions for infants10 43 and emotional and social support for mothers at the time of and following diagnosis. Furthermore, these mothers may need to be fast-tracked into services, given the particular double vulnerability of HIV and teen pregnancy.…”
Section: Discussionmentioning
confidence: 99%